Autopercepción y relaciones interpersonales en un grupo de mujeres víctimas de violación sexual a través del psicodiagnóstico de Rorschach - Fernández Godenzi, Adriana (2009)
The aim of this study was to identify the characteristics of the Rorschach clusters of self-perception and interpersonal relationships in a group of women victims of rape. For this purpose we used the Rorschach Psychodiagnostic Test, a sociodemographic questionnaire and information about the rape episode. Significant and highly significant differences were found between the women victims of rape and the comparative group in several Rorschach variables from both clusters, and also in variables regarding information processing, stress management, and the Depression Index (DEPI). As for sociodemographic variables, no significant differences were found. Among the study group some significant differences were observed according to variables related to the rape episode: received social support, pregnancy due to the rape and physical damage or disease due to the rape.